Memory Narrative and Cultural Trauma in Toni Morrison’s Beloved (1987) - Allout, Hayat; Mouissa, Fattoum (University of Ammar Theledji -Laghouat, 2022)
The African American slave trade experience is one of the important phases in American history, which is a result of several sacrifices and fighting, starting from the abolition of slavery and the Civil Rights Movement to achieve selfhood and freedom. The journey toward freedom was characterized by harsh and difficult events that marked their haunting past and traumatized present, and African Americans lived with physical, psychological, and emotional impacts. Toni Morrison's Pulitzer-winning novel Beloved depicts the traumatic experience of African Americans in America, where she focuses on the historical, emotional and psychological impacts of slavery, which certain psychologists, namely Sigmund Freud and Joseph Breuer had examines and studied in their works. This dissertation sheds light on the experience of African Americans’ journey to freedom and self-determination. Adding to the analysis of cultural trauma and memory narrative in Morrison’s Beloved,the work questions the role of memory in the history of black slaves and its association with the process of self-realization for individuals and community on whole. Thus, the main objective of this research is to highlight the relationship between cultural trauma and memory narrative and to illustrate the psychological destructive impacts as it points to the process of collective healing in Toni Morrison’s Beloved